Effect of temperature on liposome structures studied using EPR spectroscopy. Issue 1 (2005) - Sułkowski Sułkowski, W.W. W.W.; Pentak Pentak, D. D.; Korus Korus, W. W.; Sułkowska Sułkowska, A. A.
Abstract : The effect of temperature on liposome structures has been investigated by means of electron paramagnetic resonance spectroscopy with the use of the spin labelling technique. The EPR spectra were recorded on a Bruker EMX spectrometer at the X band in the temperature range 300–340 K. Liposomes were prepared from L‒α‒phosphatidylcholine dipalmitoyl (1, 2‒dihexadecanoyl‒sn‒glycerol‒3‒phosphocholine) 99% (DPPC), DL‒α‒phosphatidylcholine dimyristoyl (1, 2‒ditetradecanoyl‒rac‒glycerol‒3‒phosphocholine) 99% (DMPC) and cholesterol (5‒cholesten‒3β‒ol) 99+% to constitute the membrane. The spin marker, 2‒(3carboxypropyl)‒4, 4‒dimethyl‒2‒tridecyl‒3‒oxazolidinyloxyl free radical (5‒DOXYL), placed in a liposome membrane, allows for observation of structural changes in liposomes with temperature increase. The changes of rotational correlation time and order parameter values with increasing temperature result from the motion rise of the spin probe. The intensity of the EPR signal of 5‒DOXYL gives us information about membrane fluidity.